Berberine Ameliorates Periodontal Bone Loss by Regulating Gut Microbiota. (January 2019) - Jia, X.; Jia, L.; Mo, L.; Yuan, S.; Zheng, X.; He, J.; Chen, V.; Guo, Q.; Zheng, L.; Yuan, Q.; Xu, X.; Zhou, X.
Postmenopausal osteoporosis (PMO) is a risk factor for periodontitis, and current therapeutics against PMO prevent the aggravated alveolar bone loss of periodontitis in estrogen-deficient women. Gut microbiota is recognized as a promising therapeutic target for PMO. Berberine extracted from Chinese medicinal plants has shown its effectiveness in the treatment of metabolic diseases such as obesity and diabetes via regulating gut microbiota. Here, we hypothesize that berberine ameliorates periodontal bone loss by improving the intestinal barriers by regulating gut microbiota under an estrogen-deficient condition. Experimental periodontitis was established in ovariectomized (OVX) rats, and the OVX-periodontitis rats were treated with berberine for 7 wk before sacrifice for analyses. Micro–computed tomography and histologic analyses showed that berberine treatment significantly reduced alveolar bone loss and improved bone metabolism of OVX-periodontitis rats as compared with the vehicle-treated OVX-periodontitis rats. In parallel, berberine-treated OVX-periodontitis rats harbored a higher abundance of butyrate-producing gut microbiota with elevated butyrate generation, as demonstrated by 16S rRNA sequencing and high-performance liquid chromatography analysis. Berberine-treated OVX-periodontitis rats consistently showed improved intestinal barrier integrity and decreased intestinal paracellular permeability with a lower level of serum endotoxin. In parallel, IL-17A-related immune responses were attenuated in berberine-treated OVX-periodontitis rats with a lower serum level of proinflammatory cytokines and reduced IL-17A + cells in alveolar bone as compared with vehicle-treated OVX-periodontitis rats. Our data indicate that gut microbiota is a potential target for the treatment of estrogen deficiency–aggravated periodontal bone loss, and berberine represents a promising adjuvant therapeutic by modulating gut microbiota.